Microrna expression profiling in tears of children with vernal keratoconjunctivitis - Huda, Syed Nazmul (2022)
Vernal keratoconjunctivitis (VKC) is a chronic conjunctival inflammatory condition usually affecting children. It is often present with severe manifestations leading to corneal scar and blindness. Tears contain diverse concentrations of microRNAs (miRNAs), which are small non-coding RNA molecules regulating various cellular processes in various eye diseases. In this study we aim to generate miRNA expression profile in tears of children with VKC in comparison to controls and evaluate these miRNAs as the potential diagnostic biomarkers of VKC (phase II). However, through a pilot study, we initially investigated the optimal miRNA quantity in tears among three sampling groups, namely, unfractionated whole tears, whole-tear-derived exosomes, and exosome-depleted (phase I). This was an experimental case-control study conducted at Ophthalmology Clinic, Hospital Universiti Sains Malaysia, from January 2020 till December 2020. Phase I of the study involved normal subjects while phase II involved children with clinical diagnosis of VKC and control. RNA isolation was performed using the miRNeasy Micro Kit and quantification through Bioanalyzer RNA 6000 nano kit and Small RNA kit. VKC and control samples were screened for miRNAs expression using Agilent microarray technique. The unfractionated whole tears sampling group yielded better and optimal miRNA concentrations. Microarray results revealed a total of 51 miRNAs that were differentially expressed among children with VKC and controls. Out of these miRNAs, 48 were up-regulated and three were down-regulated. The hsa-miR-1229-5p, hsa-miR-6821-5p, and hsa-miR-6800-5p were the three top up-regulated miRNAs, while the miRNAs, hsa-miR-7975, hsa-miR-7977, and hsa-miR-1260a were the three down-regulated miRNAs. All the 48 up-regulated miRNAs can be used as the potential diagnostic miRNA biomarkers for VKC due to their higher discriminatory area under the curve (AUC) values. The miRNA target prediction analysis has determined multiple gene targets out of which 16 overlapping target genes (ARHGEF5, CCL22, CD276, LGALS9, MIF, PGF, PTGDS, PTGER, B3GAT1, SOCS3, ICOSLG, TGM2, MMP25, NGFR, FOXP3, and HRH1) were known to play role in causing conjunctival inflammation. The oxidative phosphorylation, glycolysis/gluconeogenesis, and amino sugar and nucleotide sugar metabolism were the top three KEGG pathways involved. In conclusion, miRNAs from unfractionated whole tears were differentially expressed among children with VKC and controls. Once validated, these miRNAs could serve as potential diagnostic biomarkers for VKC and provides insights into the pathogenesis of VKC.